CT and MR in infants with pericerebral collections and macrocephaly: benign enlargement of the subarachnoid spaces versus subdural collections. - Wilms, G; Vanderschueren, G; Demaerel, P H; Smet, M H; Van Calenbergh, F; Plets, C; Goffin, J; Casaer, P (American Journal of Neuroradiology, 1993)
PURPOSE To compare CT and MR in the differentiation of benign enlargement of the subarachnoid spaces and subdural collections in infants with macrocephaly.METHODS MR was performed in 19 infants with macrocephaly, showing bifrontal enlargement of the subarachnoid spaces on CT.RESULTS In 11 patients, a single fluid layer could be distinguished on MR of the pericerebral collections, suggesting benign enlargement of the subarachnoid spaces. In eight patients, two separate layers were clearly differentiated, an outer layer that was hyperintense on all sequences and an inner layer with the same intensity as the cerebrospinal fluid. This indicated the presence of subdural collections. These collections were mainly frontal in six and extended over the entire hemisphere in two patients. On CT, these separate lesions were seen only in three patients and missed in three others. In two final patients, CT findings were equivocal with evidence of membrane formation within the hypodense collections. In seven patients with a subdural collection, subdural-external drainage was performed. In three patients, the collection was hemorrhagic. The protein content of the fluid showed a mean of 1381.7 +/- 785.6 mg/dL. The MR and surgical findings of a subdural collection correlated with the absence of a family history of macrocrania, an age under 5 months, and acute clinical signs of vomiting, somnolence, and hypotonia.CONCLUSION MR appears essential in the differential diagnosis between benign enlargement of the subarachnoid spaces and subdural collections in infants.